Review of selected features of hausa vernacular architecture, case study of Dakali and Zaure in Jos, Plateau State, Nigeria - N. A. Umaru; S. T. Adamu; M. M. Bello; Adekoyejo Babatunde Jolaoso (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
Hausa Vernacular architecture is informed and shaped by cultural and religious values, wherein, Dakali and Zaure are unique features that plays a pivotal role. Cities are metaphorically described as historically solidified environment in time and in space. Thus, depicting physical, archival and artefacts of the past and present, from which it develops the future of human civilization and cultures set in a time series continuum. Hausa vernacular architecture is gradually getting evolved through modern trends by renewing, re-ordering and replacement of these features. Therefore, there is the need for studies to be carried out extensively on or before adaptation, adoption and implementation of evolving trends, in order to conserve and preserve the Hausa man’s cultural and religious values in their architecture. The paper seeks to draw attention towards the preservation and conservation of indigenous heritages through vernacular architecture, especially with the examples from the characters of Hausa architecture, without arguing for a complete reversal to the past life styles, value and techniques that would neither be out-of-place with emerging trends and acceptability of modern technology nor be balkanized. Information was essentially extracted from relevant literature on the subject matter; adopts purposive sampling and content analysis method in the selection of study area and sample size; as well as, in the extraction of features of Hausa vernacular architecture respectively. This was complimented with field survey in the form of interviews, observation and case study. Results therefrom were discussed and descriptively presented. Findings revealed that, the identified features have remained prominent and continued to perform their expected functions. The paper conclude by underscoring the need to stimulate awareness, rejuvenate and regenerate the Hausa/Fulani vernacular architecture and cultural-heritage perceptibility through creative and integrative use of architectural designs and planning concepts and skills that will be sensitive to the rebirth of cultural symbols, relics, configurations, ornamentations as symbolic expressions depicting history, branding and conveying one message or the other, about the inhabitants for better understanding and conservation of fun-memories of the cultural/traditional values and heritages.